Role of DNA Polymerase I and the rec System in Excision-Repair in Escherichia coli - Cooper, Priscilla K. (1972)
The DNA polymerase I-deficient mutant polA1 is shown to perform an increased amount of UV-stimulated repair synthesis relative to its pol(+) parent. In contrast, a recA recB double mutant is found to perform little detectable repair synthesis. Analysis of the density distribution of sheared DNA of the recA recB mutant reveals that none of the repair synthesis in this strain is in the large repair patches previously demonstrated by us in wild-type strains. These results are interpreted in terms of a model involving both DNA polymerase I and the rec system in the excision-repair process, with polymerase I performing an efficient short patch repair and rec system enzymes producing predominantly large patches of repair synthesis.